Differential Diagnosis of Hurler and Hurler–Scheie Syndromes: Clinical Case - Nataliya V. Buchinskaya; Anastasiya O. Vechkasova; Ekaterina E. Shishunova; Yuliya S. Kravtsova; Nato D. Vashakmadze; Nataliya V. Zhurkova; Mikhail M. Kostik (Вопросы современной педиатрии)
Background. Mucopolysaccharidosis type I (MPS I) is a disease known for over 100 years. Implementation of new management approaches for MPS I requires from doctor to clearly differentiate subtypes of this disease for the effective and rational use of treatment methods. Clinical case description. Girl B. with early MPS I onset during the neonatal period. Symptoms of musculoskeletal system damage were the following: feet adduction and hip joints dysplasia. Further follow-up at the age of 6 months has shown linear growth retardation, umbilical hernia, and exudative otitis. Psychomotor development up to 1 year of age was delayed. Coarse facial features by the age 1.5 years along with orthopedic problems, exudative otitis, and umbilical hernia led to mucopolysaccharidosis diagnosis. The diagnosis of mucopolysaccharidosis type I was established according to clinical findings, enzyme diagnostics (significant decrease in lysosomal enzyme alpha-L-iduronidase activity — 0.26 μmol/l/h; reference values from 1.96), and molecular genetic testing (pathogenic variant c.208C>T (Gln70Ter) in exon 2 and nucleotide variant of unknown clinical value c.1524G>C (p.Glu508Asp) in exon 10 of IDUA gene in compound heterozygous state). Echocardiography has revealed structural changes in the mitral valve and minimal aortic insufficiency. Abdominal ultrasound has revealed signs of hepatomegaly, hydrocalycosis, right-side pyelectasia, kidneys’ sizes lesser than the age norms. Abdominal magnetic resonance imaging has shown simple kidney cysts. Conclusion. The major feature of this clinical case is the complexity of differential diagnosis between the severe form of MPS I, Hurler syndrome, and milder form, Hurler–Scheie syndrome. Molecular genetic testing has revealed the presence of the frequent pathogenic variant c.208C>T (Gln70Ter) in the IDUA gene associated with severe disease course and nucleotide variant c.1524G>C (p.Glu508Asp) with undefined clinical significance, thus, additional examination is necessary. Functional analysis of the novel variant is required to establish its role in protein function. It will help more precisely determine the disease form and predict its severity. Combination of MPS I and polycystic kidney disease in the proband is unique case.